National inception workshop: Agricultural transformation and market integration in the ASEAN region: Responding to food security and inclusiveness concerns: Viet Nam - Southeast Asian Regional Center for Graduate Study and Research in Agriculture (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2017)
The International Food Policy Research Institute (IFPRI), the Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA), and the Institute of Policy and Strategy for Agriculture and Rural Development (IPSARD) jointly organized the National Inception Workshop for Vietnam, as part of the project Agricultural Transformation and Market Integration in the ASEAN Region: Responding to Food Security and Inclusiveness Concerns. The workshop was held on 27-28 April 2017 in Hanoi, Vietnam. More than 60 experts from international organizations, government agencies, academic institutions, civil society and private sector from Vietnam, the Philippines, India, the United States of America and Italy took part in the discourse on global, regional and national perspectives on agricultural transformation and market integration in the ASEAN region vis-à-vis the Vietnam economy. The Vietnam National Inception Workshop had five objectives, namely: (1) to gain a good understanding of the structural transformation and market integration and their implications for agricultural growth and food security in Vietnam, the position/role of small farmers in ATMI, and the various initiatives to address food security and inclusiveness concerns in Vietnam; (2) to consult various stakeholders – AMS, CSOs/farmers organizations, the private sector, and research institutions, on the implementation of the ATMI project; (3) to identify priority promising commodities for regional and global value chains; (4) to develop a Country Action Plan towards the achievement of the project’s target outcomes, which are enhanced capacity of AMS to identify and design national strategies, policies, programs and national agri-food value chain investment initiatives that benefit small-scale rural producers (SSRPs); and (5) to initiate the organization of the ATMI National Project Steering Committee.